Analysis of Creative Thinking Skill Profiles and Learning Recommendations Through E-Book - Pinareswati, Arlina Dwi; Rahayu*, Yuni Sri; Yuliani, Yuliani; Satriawan, Muhammad; Ariwijaya, Toni (Jurnal Pendidikan Sains Indonesia, 2025)
Creative thinking skills (CTS) involve sensitivity to problems, consideration of new information, and the generation of unusual ideas, as well as making connections to solve environmental issues. Several studies have shown that students' CTS in Indonesia are still relatively low. Therefore, this study aims to describe the characteristics of student's CTS in biology lessons, particularly in respiratory system material related to smoking habits, and to analyze the application of e-books in improving CTS. This research method is descriptive-quantitative with the research subject 37 high school students in Gresik Regency. The instrument used was a CTS test based on indicators of fluency, flexibility, originality, and elaboration and a questionnaire of students' responses. The analysis technique used was descriptive quantitative. Data from the CTS test results were obtained based on the score rubric and then categorized based on the percentage of CTS of fluency, flexibility, originality, and elaboration indicators. Meanwhile, students' questionnaire data were obtained based on a Likert scale and then categorized based on the percentage of questionnaire results. Research data shows that students' CTS in biology lessons are still low. Fluency and flexibility indicators scored less, the originality indicator was moderate, and the elaboration indicator was not creative. This research confirms that efforts to improve students' CTS can be achieved by implementing interactive learning media, such as e-books, in biology education